u=k(1+nt)

Rewrite the equation as k(1+nt)=u.

k(1+nt)=u

Divide each term in k(1+nt)=u by k.

k(1+nt)k=uk

Cancel the common factor of k.

Cancel the common factor.

k(1+nt)k=uk

Divide 1+nt by 1.

1+nt=uk

1+nt=uk

1+nt=uk

Subtract 1 from both sides of the equation.

nt=uk-1

Divide each term in nt=uk-1 by n.

ntn=uk⋅1n+-1n

Cancel the common factor of n.

Cancel the common factor.

ntn=uk⋅1n+-1n

Divide t by 1.

t=uk⋅1n+-1n

t=uk⋅1n+-1n

Simplify each term.

Multiply uk and 1n.

t=ukn+-1n

Move the negative in front of the fraction.

t=ukn-1n

t=ukn-1n

t=ukn-1n

Solve for t u=k(1+nt)